REKONSTRUKSI POLA PIKIR HAKIM DALAM MEMUTUSKAN PERKARA KORUPSI BERBASIS HUKUM PROGRESIF - Syamsudin, M (Jurnal Dinamika Hukum, 2011)
This study aims to reveal and then reconstruct the mindset of judges in deciding corruption cases based Progressive Law. Academic question posed is whether the condition of existing as the mindset of judges in deciding cases of corruption and how to build a new construction mindset of judges based on the principles of Progressive Law. This research is classified in the tradition of non-doctrinal legal research with sosiolegal approach. Data collected by interview, observation and document study and then analyzed following the interactive model of Mattew B. Miles and A. Michael Haberman. The results of study indicate the need for new construction mindset of judges based progressive law. This is based on the empirical reality that the judge handling the case of corruption by many experienced deterioration and failure to bring the law in a fair, useful and protect the interests of society. The mindset of the judge who figured positivistic needs to be reorganized under the new progressive mindset in deciding the various legal problems that emerged recently that the more complex and complicated, especially in deciding the case of corruption. Judges at all levels of education and environmental justice needs to be improved for the judge able to resolve various legal issues properly, fairly and wisely.